1955
DOI: 10.1017/s036985210000155x
|View full text |Cite
|
Sign up to set email alerts
|

The Quantities of Herbage Eaten by Grazing Dairy Cows

Abstract: The herbage dry matter intake of grazing animals may be estimated by chemical marker and faecal analysis methods (Raymond, 1954) or by pasture sampling methods.Pasture sampling methods generally involve two main difficulties. The first is the low precision resulting from the variability of pasture yields. When intake is estimated from the difference between the yields of herbage on a given area sampled before and after the grazing period, the estimate bears the error variances of both the sample means. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

1956
1956
1987
1987

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…The coefficient of variation using the twenty-eight-quadrat technique was 11·2% which is similar to or lower than those previously reported (MacLusky, 1955;Cox et al, 1956;Davison, 1959;Olubajo and Oyenuga, 1971), possibly because of the large number of samples taken. Strip grazing a range of uniform oat crops provided favourable swards for herbage sampling and relatively precise estimates of herbage intake.…”
Section: Discussionsupporting
confidence: 80%
“…The coefficient of variation using the twenty-eight-quadrat technique was 11·2% which is similar to or lower than those previously reported (MacLusky, 1955;Cox et al, 1956;Davison, 1959;Olubajo and Oyenuga, 1971), possibly because of the large number of samples taken. Strip grazing a range of uniform oat crops provided favourable swards for herbage sampling and relatively precise estimates of herbage intake.…”
Section: Discussionsupporting
confidence: 80%
“…Although this contradicted the result for the whole feeding period, they concluded that there was a critical dry-matter content for grass, below which the dry-matter intake fell, and suggested that this lay between 24 and 28 %. MacLusky (1955) found no detectable effect of variations in water content of herbage on dry-matter intake, but only on the amount of water drunk. Ittner (1954) found that wilting of alfalfa of 20-27% dry-matter content up to 34-51 % dry-matter content did not increase the amount of dry matter eaten, nor affect the performance of the steers.…”
Section: Resultsmentioning
confidence: 66%
“…Several authors have concluded that there is no effect of DM content per se on the DM intake of herbage (MacLusky, 1955;Holmes and Lang, 1963) or other forages (Hillman et al, 1958;Moore et al, 1960;Campling and Balch, 1961;Thomas et al, 1961), but in these experiments the DM content of the forage was not reduced to very low levels. At herbage DM contents below about 180 g DM kg-' (Verite and Joumet, 1970) research has clearly demonstrated that DM intake is depressed (Duckworth and Shirlaw, 1958;Halley and Dougall, 1962;Rohr and Kaufmann, 1967).…”
Section: Introductionmentioning
confidence: 86%